2016
DOI: 10.3390/cancers8010011
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Activity of the Vascular Disrupting Agent OXi4503 against Head and Neck Cancer

Abstract: Vascular disrupting agents (VDAs) represent a relatively distinct class of agents that target established blood vessels in tumors. In this study, we examined the preclinical activity of the second-generation VDA OXi4503 against human head and neck squamous cell carcinoma (HNSCC). Studies were performed in subcutaneous and orthotopic FaDu-luc HNSCC xenografts established in immunodeficient mice. In the subcutaneous model, bioluminescence imaging (BLI) along with tumor growth measurements was performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Optical techniques are subject to attenuation at depth due to absorption and scattering of light, and thus superficial tumors are most easily detected, specifically subcutaneous, or at disease sites near the surface such as mammary fat pad ( Figure 3 ). However, light can penetrate several millimeters and effective signal is observed by BLI in deeper tissues such as the lungs [ 187 , 193 , 194 , 195 ], prostate [ 196 , 197 , 198 ], brain [ 199 , 200 ], pancreas [ 201 , 202 ], liver [ 203 , 204 ], head and neck [ 114 ], bone [ 205 , 206 ] and kidney [ 138 , 207 ] in mice. The most common implementation of BLI in oncology is simply to relate signal intensity to tumor burden and indeed several studies have shown that there is a strong correlation for untreated control tumors up to about 2 cm 3 [ 89 , 208 ].…”
Section: Imaging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical techniques are subject to attenuation at depth due to absorption and scattering of light, and thus superficial tumors are most easily detected, specifically subcutaneous, or at disease sites near the surface such as mammary fat pad ( Figure 3 ). However, light can penetrate several millimeters and effective signal is observed by BLI in deeper tissues such as the lungs [ 187 , 193 , 194 , 195 ], prostate [ 196 , 197 , 198 ], brain [ 199 , 200 ], pancreas [ 201 , 202 ], liver [ 203 , 204 ], head and neck [ 114 ], bone [ 205 , 206 ] and kidney [ 138 , 207 ] in mice. The most common implementation of BLI in oncology is simply to relate signal intensity to tumor burden and indeed several studies have shown that there is a strong correlation for untreated control tumors up to about 2 cm 3 [ 89 , 208 ].…”
Section: Imaging Technologiesmentioning
confidence: 99%
“…Some primary tumors effectively yield spontaneous metastases, which are readily observed, although the primary tumor may need to be masked for effective imaging due to relative signal intensities ( Figure 4 c,d). Dynamic BLI was initially applied to known VDAs to establish the technique, e.g., CA4P [ 209 ] ( Figure 3 and Figure 4 ), CA1P [ 114 ], DMXAA [ 134 , 210 ], BPR0L075 [ 129 ], and ATO [ 161 ]. It has also been validated by comparing changes in BLI signal against alternative technologies such as MRI [ 209 ], ultrasound [ 161 ], photoacoustics [ 92 ] and histology ( Figure 3 ), each of which has shown effectively correlated data.…”
Section: Imaging Technologiesmentioning
confidence: 99%
“…Optical techniques are subject to attenuation at depth due to absorption and scattering of light, and thus superficial tumors are most easily detected, specifically subcutaneous, or at disease sites near the surface such as mammary fat pad (Figure 3). However, light can penetrate several millimeters and effective signal is observed by BLI in deeper tissues such as the lungs [180,[187][188][189], prostate [190][191][192], brain [193,194], pancreas [195,196], liver [197,198], head and neck [113], bone [199,200] and kidney [136,201] in mice. The most common implementation of BLI in oncology is simply to relate signal intensity to tumor burden and indeed several studies have shown that there is a strong correlation for untreated control tumors up to about 2 cm 3 [89,202].…”
Section: Atp + D-luciferin + O2 -----------Luciferase ---------------mentioning
confidence: 99%
“…Some primary tumors effectively yield spontaneous metastases, which are readily observed, although the primary tumor may need to be masked for effective imaging due to relative signal intensities (Figure 4c, d). Dynamic BLI was initially applied to known VDAs to establish the technique, e.g., CA4P [203] (Figures 3 & 4), CA1P [113], DMXAA [204], BPR0L075 [128], and ATO [171]. It has also been validated by comparing changes in BLI signal against alternative technologies such as MRI [203], ultrasound [171], photoacoustics [92] and histology (Figure 3), each of which has shown effectively correlated data.…”
Section: Atp + D-luciferin + O2 -----------Luciferase ---------------mentioning
confidence: 99%
“…Some microtubule targeting agents containing TMP structures have been found to inhibit microtubule polymerization and act as effective tumor‐VDAs against cancer. CA4P (Figure 1) (Liang et al, 2016; Quan et al, 2008; Zhang et al, 2013) and its similar OXi4503 (Bothwell et al, 2016), AVE8062 (Sessa et al, 2013), colchicine analog ZD6126 (LoRusso et al, 2008), BNC‐105 (Nowak et al, 2013), CKD‐516 (Lee et al, 2010) all have 3,4,5‐trimethoxyphenyl scaffold. As a pharmacophore of Tumor‐VDAs, Trimethoxyphenyl is retained as the necessary active part, and the bridge chain in the middle can be modified with amide bond, sulfonamide bond, and so on (Herdman et al, 2016; Nguyen et al, 2012; Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%